(untitled) (ItalianoLinguadue, 2020)
La comunicazione commenta uno dei risultati ottenuti nel corso di uno studio di caso condotto presso l’Università di Bologna, nell’ambito del progetto europeo ATIAH (Approaches and Tools for Internationalisation at Home). L’obiettivo complessivo era indagare come la comunità universitaria locale (studenti, personale accademico e non accademico, responsabili delle politiche educative) concettualizzasse “l’internazionalizzazione a casa” in termini di pratiche esistenti e di prospettive future. L’analisi dei dati – raccolti tramite 9 interviste e 2 focus group – evidenzia che l’internazionalizzazione è percepita dagli intervistati come sinonimo di multilinguismo e di valorizzazione della lingua italiana. Commenteremo questo risultato alla luce del dibattito scientifico sull’internazionalizzazione delle università. Internationalisation in italian? The point of view of the academic community on multilingualism at the University of Bologna This paper comments on one of the results of a case study conducted at the University of Bologna as part of the European project ATIAH (Approaches and Tools for Internationalization at Home). The overall objective was to investigate how the local university community (students, academic and non-academic staff, educational policy makers) conceptualized “internationalization at home” in terms of existing practices and future perspectives. The analysis of the data – collected through 9 interviews and 2 focus groups – shows that internationalization is perceived by the interviewees as synonymous with multilingualism and the enhancement of the Italian language. We discuss this result in light of the scientific debate on the internationalization of universities.